PENGARUH SISTEM PENGGAJIAN DAN UPAH LEMBUR TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN PT. ANPING SEAFOOD INDONESIA - Marshanda Twain Mukuan; Prisca Patricia Liem; Gebriany Pirade Wenur (LPPM Sekolah Tinggi Ilmu Ekonomi Petra Bitung, 2026)
This study aims to examine the effect of the Payroll System and Overtime Pay on Employee Performance at PT. Anping Seafood Indonesia. The research employed a quantitative approach with an associative research design. The sample consisted of 72 operational employees selected from a population of 103 employees. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that the Payroll System has a positive and significant effect on Employee Performance, while Overtime Pay does not have a significant partial effect on Employee Performance. However, simultaneously, the Payroll System and Overtime Pay significantly affect Employee Performance. The coefficient of determination (R²) of 74.7% indicates that variations in Employee Performance can be explained by these two variables, while the remaining 25.3% is influenced by other factors outside the research model. These findings suggest that the Payroll System is the most dominant factor affecting Employee Performance at PT. Anping Seafood Indonesia.